PkM: Pelatihan Peningkatan Skill Siswa Sekolah Kejuruan pada Pembuatan Game Sederhana berbasis Android - Agus Perdana Windarto; M Mesran; Anjar Wanto (LPPM STIKOM Tunas Bangsa, 2022)
In accordance with the title of this community service program (P2M), the method of applying science and technology is in the form of android training in making simple games. Skills training activities are supported by lectures, questions and answers, and of course hands-on practice in the computer laboratory. The training module will be given to participants as a tool for practical activities in the laboratory. The purpose of implementing this community service program is to improve the skills of Pematangsiantar Exemplary Private Vocational School Students, by making simple android-based games for Pematangsiantar Exemplary Private Vocational High School Students, so as to minimize the gap between the skill levels of the Pematangsiantar Exemplary Private Vocational High School students. with the needs of the real world of work. From the evaluation results and the findings obtained during the implementation of this P2M activity, it can be concluded that this P2M program has been able to provide enormous and targeted benefits for Pematangsiantar Exemplary Private Vocational High School Students in this activity. This form of training is a very effective form of providing refreshment and additional insight and new knowledge in the field of information technology outside of the learning process received in their respective schools.